2018
DOI: 10.1177/0003489418759113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fentanyl Nasal Packing Treatment on Patients With Acute Postoperative Pain After Nasal Operation: A Randomized Double-Blind Controlled Trial

Abstract: Fentanyl group showed significantly reduced postoperative pain without serious adverse effects. We suggest that topical fentanyl application to nasal packs can be a useful method to reduce pain during the early postoperative period after endoscopic sinus surgery and septoplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…In a randomized clinical trial by Moeller et al, no differences in postoperative epistaxis rates were found in patients who received intravenous ketorolac compared to intravenous fentanyl during FESS procedures . Kim et al proposed an alternative technique utilizing topical anesthesia; this study demonstrated significantly lower reported pain and increased patient satisfaction following FESS and septoplasty procedures when patients were given topical fentanyl‐soaked nasal packing compared to saline soaked packing …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a randomized clinical trial by Moeller et al, no differences in postoperative epistaxis rates were found in patients who received intravenous ketorolac compared to intravenous fentanyl during FESS procedures . Kim et al proposed an alternative technique utilizing topical anesthesia; this study demonstrated significantly lower reported pain and increased patient satisfaction following FESS and septoplasty procedures when patients were given topical fentanyl‐soaked nasal packing compared to saline soaked packing …”
Section: Discussionmentioning
confidence: 99%
“…18 Kim et al proposed an alternative technique utilizing topical anesthesia; this study demonstrated significantly lower reported pain and increased patient satisfaction following FESS and septoplasty procedures when patients were given topical fentanyl-soaked nasal packing compared to saline soaked packing. 19 Limitations of this study include the use of artificially stratified categories for opioid use. In addition, the group taking more than five opioid tablets varied greatly in terms of opioid intake.…”
Section: Discussionmentioning
confidence: 99%
“…This practice is problematic, because even a short course of opioids after minor surgery has been associated with an increased likelihood of persistent opioid use at 1 year, and the risk of long‐term opioid use increases with each additional day of opioids supplied beyond 3 days . Despite recent calls to action by the Centers for Disease Control and Prevention for changes in opioid‐prescribing behaviors, and numerous studies supporting the effectiveness of nonopioid analgesia for postoperative pain control following ESS, most otolaryngologists continue to prescribe opioids following this procedure . For those who prefer to continue prescribing opioids, our study, along with others in the literature, suggest that small opioid doses are sufficient for controlling postoperative pain after ESS .…”
Section: Discussionmentioning
confidence: 99%
“…Four studies involved only sinus surgeries, eight involved only septal surgeries, and three involved sinus surgeries, septal surgeries, as well as a combination of the two. One study 8 used fentanyl as topical anesthetic agent, five studies compared multiple anesthetics to placebo, and ten studies evaluated the effects of a single anesthetic agent. Ten studies provided information regarding postoperative pain reduction, of which seven 8 , 9 , 10 , 11 , 12 , 13 , 14 were RCTs providing complete data and were included for statistical analysis.…”
Section: Resultsmentioning
confidence: 99%
“…One study 8 used fentanyl as topical anesthetic agent, five studies compared multiple anesthetics to placebo, and ten studies evaluated the effects of a single anesthetic agent. Ten studies provided information regarding postoperative pain reduction, of which seven 8 , 9 , 10 , 11 , 12 , 13 , 14 were RCTs providing complete data and were included for statistical analysis. Seven studies evaluated pain upon packing removal, only two 15 , 16 of which were RCTs with complete data included for statistical analysis.…”
Section: Resultsmentioning
confidence: 99%